Interfaith Marriage in the Perspective of Maqasid al-Sharia'ah: Normative-Empirical Study of Interfaith Marriage Practices in the Tolaki Society - sulaemang, sulaemang; Sukardi, Akhmad; Nasruddin, Nasruddin (Al-'Adl, 2025)
Interfaith marriage in Indonesia's Muslim community is a phenomenon that continues despite the Qur'an explicitly prohibiting it. Previous studies have generally been normative-doctrinal without any empirical data, and there have been no studies that have analyzed this phenomenon in the Tolaki community through the framework of maqasid al-shari'ah. Using an interdisciplinary normative-empirical qualitative approach, this study identified 14 interfaith couples in three villages in Wolasi District, South Konawe Regency. The findings show that this phenomenon is a product of structural inconsistency between Islamic law, the Kalo Sara customary value system, and the positive law of the state. The maqasid analysis identified threats to hifz al-din through the case of riddah, to hifz al-nasl through the uncertainty of the child's religious identity, and to hifz al-nafs through chronic value conflicts. The novelty of this research lies in the disclosure of the epistemic tension between Kalo Sara and Islamic norms, as well as in the offer of a maqasid-based reformative framework for strengthening marriage governance in pluralistic Muslim communities.